EXCHANGE INTERVENTION EFFECT IN COLOMBIA: 2004-2006 - Hernández Monsalve, Mauricio A.; Mesa Callejas, Rannón Javier Javier (Revista Venezolana de Análisis de Coyuntura, 2016)
This articie measures the effectiveness of the exchange interventions executed exerted by theColombian Central Bank between 2004-2006 from a relative measure for the size of such interventionsand its effects on the mean and variance of the nominal exchange rate in the country in suchperiod. The obtained results by means of a relative index of intervention, a GARCH estimation andan impulse-response function, indicate that such interventions had littie and transitory effects in thelevel and variance of the exchange rate, presenting several day delays and being rapidly discountedby the market. Likewise, it is shov^m that such Interventions, executed in a moment when astrong appreciation process of the Colombian peso happened, did not generate inflationary pressuresand could moderate, but not revert, the peso/dollar revaluatlon tendency .